GEAR WHEELS THE PROCESSED BY ELECTRICAL EROSION - MARCEL S.POPA; IOAN BADIU (Fiabilitate şi Durabilitate)
For low tooth loads and low peripheral speeds between 0.3 and 2 m / s are chosen based alloys and steels, gray cast iron. In industry are preferable ferrous alloys: bronze, brass and aluminum alloys, and where speeds and demands are low gears are made of sheet steel or alloys. Wheel group required less include some hand-operated mechanisms, such as jacks, some trolls. These wheels are larger and they are made of alloy steel, semi-hard and sometimes gray cast iron FC250, FC300.